A STAT4 variant increases liver fibrosis risk in Caucasian patients with chronic hepatitis B. Issue 5 (2nd July 2018) - El Sharkawy, R.; Thabet, K.; Lampertico, P.; Petta, S.; Mangia, A.; Berg, T.; Metwally, M.; Bayoumi, A.; Boonstra, A.; Brouwer, W. P.; Smedile, A.; Abate, M. L.; et al.
Summary: Background: Host genetic modifiers of the natural history of chronic hepatitis B (CHB) remain poorly understood. Recently, a genome‐wide association study (GWAS)‐identified polymorphism in the STAT4 gene that contributes to the risk for hepatocellular carcinoma (HCC) was shown to be associated with the full spectrum of hepatitis B virus (HBV) outcomes in Asian patients. However, the functional mechanisms for this effect are unknown and the role of the variant in modulating HBV disease in Caucasians has not been investigated. Aims: To determine whether STAT4 genetic variation is associated with liver injury in Caucasian patients with CHB and to investigate potential mechanisms mediating this effect. Methods: STAT4 rs7574865 was genotyped in 1085 subjects (830 with CHB and 255 healthy controls). STAT4 expression in liver, PBMCs and NK cells, STAT4 phosphorylation and secretion of interferon‐gamma (IFN‐γ) according to STAT4 genetic variation was examined. Results: STAT4 rs7574865 genotype was independently associated with hepatic inflammation (OR: 1.42, 95% CI: 1.07‐2.06, P  = 0.02) and advanced fibrosis (OR: 1.83, 95% CI: 1.19‐2.83, P  = 0.006). The minor allele frequency of rs7574865 was significantly lower than that in healthy controls. rs7574865 GG risk carriers expressed lower levels of STAT4 in liver, PBMCs and in NK cells, while NK cells from patients with the risk genotype had impaired STAT4 phosphorylation following stimulation with IL‐12/IL‐18 and a reduction in secretion of IFN‐γ. Conclusion: Genetic susceptibility to HBV persistence, hepatic inflammation and fibrosis in Caucasians associates with STAT4 rs7574865 variant. Downstream effects on NK cell function through STAT4 phosphorylation‐dependent IFN‐γ production likely contribute to these effects.